Systematics of the color-polymorphic spider genus Cybaeolus, with comments on the phylogeny of the family Hahniidae (Araneae): Phylogenetic dataset, trees and images at full resolution - Ramirez, Martin Javier (2024)
Original images and phylogenetic analysis of the spiders of the genus Cybaeulus, with outgroups in the marronoid clade. Data from six DNA markers, analyzed with maximum likelihood and parsimony.